2023
DOI: 10.1038/s41598-023-41399-5
|View full text |Cite
|
Sign up to set email alerts
|

Antibody response in elderly vaccinated four times with an mRNA anti-COVID-19 vaccine

Alexander Rouvinski,
Ahuva Friedman,
Saveliy Kirillov
et al.

Abstract: The humoral response after the fourth dose of a mRNA vaccine against COVID-19 has not been adequately described in elderly recipients, particularly those not exposed previously to SARS-CoV-2. Serum anti-RBD IgG levels (Abbott SARS-CoV-2 IgG II Quant assay) and neutralizing capacities (spike SARS-CoV-2 pseudovirus Wuhan and Omicron BA.1 variant) were measured after the third and fourth doses of a COVID-19 mRNA vaccine among 46 elderly residents (median age 85 years [IQR 81; 89]) of an assisted living facility. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 41 publications
(113 reference statements)
1
0
0
Order By: Relevance
“…Our cohort study indicated a beneficial effect of booster vaccination on the magnitude of anti-SARS-CoV-2 IgG and IgA antibodies. Similar outcomes have been found by other studies [ 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. Each additional dose contributed cumulatively and maintained a high concentration of existing antibodies [ 15 , 16 , 17 , 18 ].…”
Section: Discussionsupporting
confidence: 92%
“…Our cohort study indicated a beneficial effect of booster vaccination on the magnitude of anti-SARS-CoV-2 IgG and IgA antibodies. Similar outcomes have been found by other studies [ 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. Each additional dose contributed cumulatively and maintained a high concentration of existing antibodies [ 15 , 16 , 17 , 18 ].…”
Section: Discussionsupporting
confidence: 92%